(untitled) ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2025)
This article presents a comparative study of lexical units related to the national customs of different peoples. The research examines terms associated with ceremonies, festivals, clothing, food, and cultural practices as key indicators reflecting the intrinsic connection between language and culture. Words related to customs in English, Uzbek, Russian, and Japanese are compared from semantic, cultural, and translational perspectives, highlighting both universal and unique features. The findings reveal that vocabulary connected to national customs not only preserves the historical and cultural memory of nations but also plays an important role in intercultural communication.